Theranostic gold-magnetite hybrid nanoparticles for MRI-guided radiosensitization. (4th June 2018) - Maniglio, D; Benetti, F; Minati, L; Jovicich, J; Valentini, A; Speranza, G; Migliaresi, C
Abstract: The main limitation of drug-enhanced radiotherapy concerns the difficulty to evaluate the effectiveness of cancer targeting after drug administration hindering the standardization of therapies based on current radiosensitizing compounds. The challenge regards the development of systems able to combine imaging and radiotherapy enhancement in order to perform highly reliable cancer theragnosis. For these reasons, gold-magnetite hybrid nanoparticles (H-NPs) are proposed as innovative theranostic nanotools for imaging-guided radiosensitization in cancer treatment. In this work we propose a novel method for the synthesis of hydrophilic and superparamagnetic Tween20-stabilized gold-magnetite H-NPs. Morphology and chemical composition of nanoparticles were assessed by transmission electron microscopy, x-ray diffraction analysis and ion-coupled plasma optical emission spectroscopy. Colloidal stability and magnetic properties of nanoparticles were determined by dynamic light scattering and magnetometry. The potentialities of H-NPs for magnetic resonance imaging were studied using a human 4T-MRI scanner. Nanoparticles were proven to induce concentration-dependent contrast enhancement in T2*-weighted MR-images. The cytotoxicity, the cellular uptake and the radiosensitization activity of H-NPs were investigated in human osteosarcoma MG63 cell cultures and murine 3T3 fibroblasts, using specific bioassays and laser scanning confocal microscopy. H-NPs did not exhibit significant toxicity and were demonstrated to be internalized by cells. A significant x-ray enhancement at specific H-NPs exposure concentrations was evidenced on MG63 cell line.